Imam Hussain Impetuosity: An Orientalist’s Misrepresentation And Distortion Of The Ashura Renaissance (Journal of Namibian Studies : History Politics Culture, 2023)
Considering the place of Orientalists and their importance in the references of researchers, non-Muslim, and even Muslim audiences, it is necessary to review their work, especially from a Shiite point of view. The current study aims to correct the Orientalist thought and ideology about the renaissance of Imam Hussain and his march to Karbala, which has been referred to as impetuous in Encyclopaedia and other Orientalist books. The present article is the result of library-based research with a descriptive, analytical, and critical approach. It has been conducted around some of the reasons and arguments that prove that the Renaissance of Imam Hussain was neither impetuous nor reckless but a decision full of bravery, sacrifice, wisdom, and a stand against oppression. While buttressing this proof, some points were analyzed, including the leadership and immaculacy of Imam Hussain, the goals and objectives of Imam Hussain for the Renaissance, his adherence to the Sunnah, his appointment of Minister/Emissary, and the prophecy and forecasting of his martyrdom. In conclusion, it became clear that Imam Al-Hussein (AS) did not go out to Karbala impetuously or recklessly, but rather went out bravely and sacrificed his life to defend the religion of God and the religion of his grandfather (PBUH) and his father (AS).